The Effects of Positive Self-talk Training Program on Emotional Intelligence of the First Year Students of Nakhon Ratchasima Rajabhat University - Karnkha, Orapun; haithani, Prayut (Ratchaphruek Journal, 2014)
This quasi-experimental research was conducted to study the effects of positive self-talk training program on emotional intelligence of the first year students of Nakhon Ratchasima Rajabhat University. The samples were 10 students in English program and 10 students in Music program. All 20 students studied in the second semester of academic year 2013. The experiment was used as instruments, which were1) positive self-talk training program for 2 weeks, 4 days a week from Tuesday-Friday at 60 minutes a day, and 2) an evaluation format of emotional intelligence for people aged 18-60 year. The data collection was divided into 2 phases according to the length of pretest and posttest, and they were then analyzed by t-test. The results showed that 1 . Posttest experimental group students had an average score of emotional intelligence higher thanbefore the experimentat .01 level of significance. 2 . Posttest experimental group students had an average score of emotional intelligence higher than these of the control groupat .01 level of significance.